Comparison of Artificial Neural Networks and ARMA Models for Stock Price Prediction : Empirical study of the U.S. markets 2016-2021 - Liiman, Dan (My University, 2023)
Machine learning algorithms have shown promising ability in pattern identification and prediction tasks across a range of applications. Various machine learning techniques have been used in an increasing number of studies in recent years to analyse financial time series. The ability of machine learning techniques to handle complicated and nonlinear data sets, as well as the growing availability of data and processing power, have advanced research in the field. Even though machine learning techniques are now often utilized for predicting financial time series, the outcomes have been contradictory when compared with traditional econometric models. This study investigates whether neural networks can outperform traditional econometric model in a stock price prediction. A multilayer perceptron (MLP), a recurrent neural network (RNN), and a long short-term memory (LSTM) are compared with the autoregressive integrated moving average (ARIMA) model and evaluated for their ability to predict future closing prices. This study emphasizes the significance of choosing suitable models for time series forecasting and offers insights into the benefits and drawbacks of these widely used approaches. The indices used in the study are S&P 500, Dow Jones Industrial Average, NASDAQ Composite Index, and Russel 2000. Observations will be obtained from Refinitiv Eikon Datastream and the full research sample extends from the 4th of January 2016 through the 15th of December 2021. The series are divided into study periods, with 1200 days for in-sample training and 300 days for out-of-sample predictions. The out-of-sample covers the period from the 8th of October 2020 through the 15th of December 2021. The model performance is measured by using root mean squared error (RMSE) metric. Furthermore, a trading strategy is carried out to reveal possible profitable attributes of the models. When evaluating neural networks RNN and LSTM are more accurate than MLP model based on RMSE when forecasting prices. However, the ARIMA model is generally the most accurate out of all the models. When forecasting performance is tested using a trading strategy LSTM outperforms other models before transaction costs are taken into account excluding S&P 500 index. Because of the non-stationary data, MLPs were unable to capture the rising trend and proceed to give predictions that would lead to negative annualized returns even when trading costs were not accounted for. Nevertheless, none of the evaluated models outperform a straightforward buy-and-hold strategy in terms of profitability when transaction costs are taken into consideration

Koneoppimisen algoritmit ovat osoittaneet kykyä esimerkiksi tunnistamisessa ja ennustamisessa useilla eri aloilla. Viime vuosina yhä useammassa tutkimuksessa on käytetty erilaisia koneoppimistekniikoita taloudellisten aikasarjojen analysoimiseen. Koneoppimistekniikoiden kyky käsitellä monimutkaisia ja epälineaarisia aineistoja, tiedon saatavuuden ja laskentatehon kasvu ovat edesauttaneet kehitystä tieteenalalla. Vaikkakin koneoppimistekniikoita käytetään nykyään usein taloudellisten aikasarjojen ennustamiseen, tulokset ovat olleet ristiriitaisia, kun vertailun kohteena on ollut klassinen ekonometrinen malli. Tässä opinnäytetyössä tarkastellaan, pystyvätkö neuroverkotverkot suoriutumaan paremmin kuin klassinen ekonometrinen malli hintojen ennustamisessa. Monikerroksista perseptroniverkkoa (MLP), takaisinkytkettyä neuroverkkoa (RNN) ja pitkää lyhytkestoista muistia (LSTM) verrataan autoregressiiviseen integroituun liukuvan keskiarvon (ARIMA) malliin ja arvioidaan niiden kykyä ennustaa tulevia päivittäisiä hintoja. Tutkimus korostaa, kuinka tärkeää on valita sopivat mallit aikasarjojen ennustamiseen, ja tarjoaa vastauksia näiden laajasti käytettyjen lähestymistapojen hyödyistä ja haitoista. Opinnäytetyössä käytetyt indeksit ovat S&P 500, Dow Jones Industrial Average, NASDAQ Composite Index ja Russel 2000. Havainnot on ladattu Refinitiv Eikon Datastreamista, koko tutkimusnäyte on ajanjaksolta 4.1.2016–15.12.2021. Aikasarjat jakautuvat opintojaksoihin, joissa 1200 päivää on koulutusta varten ja 300 päivää ennusteita varten. Ennustamisen ajanjakso kattaa 8.10.2020–15.12.2021. Mallien suorituskykyä mitataan keskineliövirheen neliöjuurella (RMSE). Lisäksi toteutetaan kaupankäyntistrategia, joka paljastaa mallien taloudellisen kannattavuuden. Työn tulokset osoittavat, että neuroverkkoja arvioitaessa RMSE:n avulla, RNN ja LSTM ovat MLP-verkkoa tarkempia hintojen ennustamisessa. ARIMA-malli on kuitenkin yleisesti kaikista malleista tarkin. Kun ennakointikykyä testataan kaupankäyntistrategian avulla, ennen kaupankäyntikulujen huomioimista LSTM on muita malleja parempi lukuun ottamatta S&P 500-indeksin kohdalla. Ei-stationaaristen aikasarjojen vuoksi MLP-verkot eivät pystyneet kaappaamaan nousevaa trendiä ja antoivat ennusteita, jotka johtaisivat negatiivisiin vuosituottoihin, vaikka kaupankäyntikustannuksia ei otettaisi huomioon. Yksikään arvioiduista malleista ei kuitenkaan ole kannattavampi kuin pelkkä osta-ja-pidä-strategia kun kaupankäyntikulut otetaan huomioon.
Keywords: machine learning, deep learning, neural networks, forecasting, stock market